A pre-clerkship simulation-based procedural skills curriculum: decreasing anxiety and improving confidence of procedural skill performance - Battaglia, Frank; Ivankovic, Victoria; Merlano, Maria; Patel, Vishesh; Sayed, Céline; Wang, Hao; McConnell, Meghan; Rastogi, Nikhil (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Introduction: Pre-clerkship procedural skills training is not yet a standard across Canadian medical school curricula, resulting in limited exposure to procedures upon entering clerkship. While simulated skills training has been documented in the literature to improve performance in technical ability, anxiety and confidence have yet to be investigated despite their documented impact on performance and learning. This study therefore aims to evaluate the effect of pre-clerkship procedural skills training on medical student anxiety and confidence.Methods: A procedural skills training program was designed based on an evidence-based near-peer, flipped classroom model of education. Ninety-two second-year medical students volunteered for the study. Fifty-six were randomized to the training group, and 36 were randomized to the control group. Students in the training group attended seven procedural skills tutorials over seven months. The control group represented the average medical school student without standardized procedural training. Student anxiety and confidence were assessed at the beginning and end of the program using the State Trait Anxiety Inventory and Confidence Questionnaires.Results: Students who participated in the procedural skills program demonstrated greater reductions in their state anxiety and greater improvements in confidence compared to the control group.Conclusion: Longitudinal procedural skills training in the simulation setting has demonstrated improvements in anxiety and confidence among pre-clerkship medical students. These added benefits to training have the potential to ease medical students’ transition into clerkship, while also contributing to a safer and more effective clinical experience. Therefore, future integration of standardized pre-clerkship procedural skills training within medical school curricula should be considered.